An outline of object-oriented philosophy. (1st June 2013) - Harman, Graham
This article summarises the principles of object-oriented philosophy and explains its similarities with, and differences from, the outlook of the natural sciences. Like science, the object-oriented position avoids the notion (quite common in philosophy) that the human–world relation is the ground of all others, such that scientific statements about the world would only be statements about the world as it is for humans. But unlike science, object-oriented metaphysics treats artificial, social, and fictional entities in the same way as natural ones, and also holds that the world can only be known allusively rather than directly.